Taiwanese Language Education : An Analysis of the Linguistic Human Rights of Indigenous Minority Communities - Salmijärvi, Riku (My University, 2026)
This thesis examines the Taiwanese education system in relation to Indigenous minority students and their endangered heritage languages. The aim of the thesis is to analyze how the linguistic human rights of Indigenous minorities are realized in the national education system, and how that affects Indigenous language revitalization and student learning outcomes. This was accomplished through a comparative literature review of 8 publications that cover Taiwan’s Indigenous education from different angles. Issues in education are thematically grouped and analysed together and in relation to linguistic human rights. Through this analysis, the thesis finds that the Taiwanese education system does not properly support the linguistic human rights of Indigenous minority communities, and language revitalization efforts have largely been ineffective. As such, I argue that aligning education to respect the linguistic human rights of Indigenous students would also lead to practical improvements in education and language revitalization. Most importantly, mother tongue medium education ought to be implemented for minority groups to respect their rights as well as improve language learning outcomes.
Keywords: Taiwanese education; Indigenous languages; linguistic human rights; minority language education; language revitalization